2012
DOI: 10.1590/s1984-82502012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Sustained virological response to treatment of chronic hepatitis C with peginterferon alfa and ribavirin

Abstract: This study aimed to evaluate the rate of sustained virological response (SVR) and the clinical and treatment characteristics of patients with chronic hepatitis C (CHC). A retrospective uncontrolled cohort study was conducted among patients who received treatment for CHC between 2005 and 2008 attended at the Center for the Application and Monitoring of Injectable Medications, in Florianopolis, SC, Brazil. The inclusion criteria were: patients over 18 years of age, with a confirmed diagnosis of chronic hepatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…The improvement of SVR was expected with the triple therapy, however, the results was similar to those achieved with INF-PEG 2a/2b + RBV regimen-based. Brazilian studies that analyzed the dual therapy showed SVR rates between 40-50% 28 , 29 . Additionally, as shown in the results, the public investment to acquire the triple therapy was much higher when compared with the dual therapy acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of SVR was expected with the triple therapy, however, the results was similar to those achieved with INF-PEG 2a/2b + RBV regimen-based. Brazilian studies that analyzed the dual therapy showed SVR rates between 40-50% 28 , 29 . Additionally, as shown in the results, the public investment to acquire the triple therapy was much higher when compared with the dual therapy acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…A ausência de informação sobre vários indicadores de qualidade das amostras é preocupante porque, há mais de duas décadas, publicações nacionais e internacionais insistem nesses importantes pré-requisitos para o aprimoramento do diagnóstico, do estadiamento e da escolha terapêutica nos casos de hepatites crônicas. [18][19][20] Da mesma forma, outros autores identificaram, em seu estudo, 21 pacientes com laudos de biópsias hepáticas provenientes de diversos laboratórios, apontando que as diferentes características desses laboratórios e a não uniformização dos laudos são condições capazes de afetar diretamente a prescrição médica inicial. Na última década, o Programa Nacional para a Prevenção e o Controle das Hepatites Virais do Ministério da Saúde (PNHV/SVS/MS) empenhou-se na promoção de numerosos cursos, simpósios e demais ações de ensino continuado, viabilizando a confecção e distribuição do Atlas de Patologia Hepática.…”
Section: Discussionunclassified
“…Dificuldades semelhantes em relação à obtenção de informações foram apontadas por Rosa e cols. 21 ao analisarem pacientes em tratamento no município de Florianópolis, capital do estado de Santa Catarina.…”
Section: Discussionunclassified